Madrasah Management Based on Boarding School - Ahmad Sabri; Vevi Gusmida; Hidayati (Global Writing Academica Researching & Publishing, 2023)
The purpose of this study was to determine program planning, program implementation and evaluation of the Boarding School program at the State Madrasah Aliyah. This type of research is field research using descriptive qualitative methods. The data sources used were the Head of Madrasah, Deputy Student Affairs and Dormitory Supervisors. Techniques and data collection through observation, interviews and documentation. Boarding School program planning at Madrasah Aliyah Negeri has been prepared based on long-term, medium and short-term planning. Implementation of the Boarding School program, namely memorizing deposits is carried out 2 times a week, tadarus every day, muhadharah every week, annisa forum every Friday, congregational prayers at the mosque, sunnah prayers, sunnah fasting and additional learning in academic fields such as Science, Mathematics, History and Language subjects English. Meanwhile in the religious field, such as Arabic, Fiqh, Al-Qur'an Hadith and SKI subjects, which are held twice a week. Evaluation of Boarding Schools at Madrasah Aliyah Negeri, in accordance with the targets in the plan. The supporting factors for the Boarding School program are the availability of Wi-Fi and competent human resources in their fields. Meanwhile, from the inhibiting factors, namely in terms of sources of funds, lack of cooperation between parents and madrasas and clashes in the Boarding School program with extracurricular madrasahs.